2011
DOI: 10.1111/j.1365-2486.2011.02541.x
|View full text |Cite
|
Sign up to set email alerts
|

Population vulnerability to climate change linked to timing of breeding in boreal ducks

Abstract: Identifying and understanding why traits make species vulnerable to changing climatic conditions remain central problems in evolutionary and applied ecology. We used spring snow cover duration as a proxy for phenological timing of wetland ecosystems, and examined how snow cover duration during spring and during the entire snow season affected population dynamics of duck species breeding in the western boreal forest of North America, 1973America, -2007 We predicted that population level responses would differ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 60 publications
5
61
0
Order By: Relevance
“…With respect to terrestrial ecosystems, snow cover, permafrost conditions, surface hydrology, and vegetation are all inter-related. For example, recent dramatic reductions in Arctic spring snow cover duration reported in and Derksen and Brown (2011) have direct effects on wildlife (for example, see Drever et al 2011). Shorter snow cover seasons are consistent with an extension of the growing season over the Arctic as discussed in Jia et al (2009), and are consistent with earlier peak stream flow, a more rapid recessional limb, and higher peak runoff volume, as reported by Shiklomanov and Lammers (2009).…”
Section: The Cryosphere As An Integrated Systemsupporting
confidence: 68%
“…With respect to terrestrial ecosystems, snow cover, permafrost conditions, surface hydrology, and vegetation are all inter-related. For example, recent dramatic reductions in Arctic spring snow cover duration reported in and Derksen and Brown (2011) have direct effects on wildlife (for example, see Drever et al 2011). Shorter snow cover seasons are consistent with an extension of the growing season over the Arctic as discussed in Jia et al (2009), and are consistent with earlier peak stream flow, a more rapid recessional limb, and higher peak runoff volume, as reported by Shiklomanov and Lammers (2009).…”
Section: The Cryosphere As An Integrated Systemsupporting
confidence: 68%
“…Previous research has suggested that drier and warmer conditions may lead to a 70%-90% loss of wetlands in the Hudson Plains [76]. Reduced duration of snow cover, associated with predicted increases in minimum greenness and decreased seasonality, will negatively impact some duck species in boreal wetlands [77]. For example, reduced flexibility in timing of breeding has been predicted to impact population levels of species such as scaups (Aythya spp.)…”
Section: Discussionmentioning
confidence: 99%
“…The differing helminth infracommunity structures observed herein occurred within a small geographical scale relative to the annual cycle of scaup, indicating that these hosts may experience frequent and rapid changes in intestinal parasite infracommunities, which may be strongly related to intermediate hosts present in diets. Global climate change and increased habitat fragmentation are of increasing concern for conservation efforts (Austin et al, 2006;Drever et al, 2012) and may affect the dispersal of hosts and parasites, thereby altering their interactions and disease dynamics at different scales (Holt & Boulinier, 2005). Considering the temporal proximity of the spring migration and breeding seasons, energetic and behavioural costs of immune responses to varying helminth infections may lead to reduced survival and/or productivity (Hanssen et al, 2004;Stafford et al, 2014).…”
Section: Spatiotemporal Assessmentmentioning
confidence: 99%